Strategies for the construction of morphinan alkaloid AB-rings: regioselective Friedel-Crafts-type cyclisations of gamma-aryl-beta-benzoylamido acids with asymmetrically substituted gamma-aryl rings - Davies, S; Goddard, E; Roberts, P; Russell, A; Smith, A; Thomson, J; Withey, J (Elsevier, 2016)
The regioselectivity of the Friedel-Crafts-type cyclisation of a range of γ-aryl-β-benzoylamido acids, bearing oxy substituents at the C(3)- and C(4)-positions of the γ-aryl ring, has been investigated. In all of the cases examined (with 3,4-dimethoxy, 3,4-methylenedioxy and 3-hydroxy-4-methoxy substituents) the Lewis acid promoted cyclisation proceeds with exclusive regioselectivity for attack at the C(6)-position rather than at the C(2)-position, and furnishes the corresponding N- and O-protected 3-amino-6,7-dihydroxy-1-tetralone derivatives. This inherent regioselectivity can be overturned by the regioselective introduction of chlorine as a blocking group for the C(6)-position; subsequent Lewis acid promoted cyclisation then proceeds with exclusive regioselectivity for attack at the C(2)-position to deliver the corresponding N- and O-protected 3-amino-5-chloro-7,8-dihydroxy-1-tetralone derivative. These complementary cyclisation protocols represent useful methods for the preparation of these benzo-fused carbocyclic ring systems, which are the functionalised AB-rings of a range of morphinan alkaloids.